Sexual Sadism and Psychopathy in Sexual Homicide Offenders: An Exploration of Their Associates in a Clinical Sample - Darjee, Rajan (International journal of offender therapy and comparative criminology, 2019)
Sexual sadism and psychopathy are often considered synonymous with sexual homicide, but there is limited research on their associates in sexual homicide offenders. Associates of dimensional measures of sexual sadism (Sexual Sadism Scale; SeSaS) and psychopathy (Psychopathy Check List-Revised [PCL-R] total, Factor 1, and Factor 2) were examined in 51 male Scottish cases. Over a third were DSM-IV (Diagnostic and Statistical Manual of Mental Disorders-IV) sexual sadists, just under a third screened in with the SeSaS, and a quarter were "Hare psychopaths." Sexual sadism and PCL-R measures were moderately associated. Sexual sadism predicted control, sexual deviance, and unusual behaviour at crime scenes; attempted homicide and having a co-accused; and multiple sexual homicides and previous sexual offending. PCL-R Factor 1 predicted violent, exploitative, and evading detection behaviours at crime scenes; completed homicide; and previous violent offending. PCL-R Factor 2 predicted impulsive behaviours at crime scenes, substance misuse, and previous general offending. Psychopathy and sexual sadism play key roles in sexual homicide, interact with each other, and determine different aspects of offences and offenders.